2017
DOI: 10.1039/c6ob02617f
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic minimalistic tryptophan zippers as a chiroptical switch

Abstract: In this paper, we presented a new design strategy for a peptide-based chiral supramolecular assembly. A series of aryl linked peptides 1a-1f were designed and synthesized. The bis-urea peptides 1a-1c self-assembled into a helical supramolecular arrangement resembling Trp zipper (Trpzip) structures present in proteins. Interestingly, a dihydrogenphosphate anion, upon binding to the assembly, could invert the chirality of the supramolecular assembly which could be reverted to the original by the addition of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…57 In another study, we designed and synthesized bis-urea peptides 37−39 that form a Trp zipper-based supramolecular helical arrangement (Figure 14a) that changed the chirality upon dihydrogen phosphate binding (Figure 14b). 58 These Trpappended bis-urea peptides (37−39) showed a vesicular assembly. MD simulation indicated that these peptides (37− 39) first assembled to a chiral Trp-zipper arrangement, which further assembled to form vesicles (Figure 14c).…”
Section: For Vesicular Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…57 In another study, we designed and synthesized bis-urea peptides 37−39 that form a Trp zipper-based supramolecular helical arrangement (Figure 14a) that changed the chirality upon dihydrogen phosphate binding (Figure 14b). 58 These Trpappended bis-urea peptides (37−39) showed a vesicular assembly. MD simulation indicated that these peptides (37− 39) first assembled to a chiral Trp-zipper arrangement, which further assembled to form vesicles (Figure 14c).…”
Section: For Vesicular Assemblymentioning
confidence: 99%
“…The addition of dihydrogen phosphate resulted in the formation of pores on the surface of the vesicles . In another study, we designed and synthesized bis-urea peptides 37 – 39 that form a Trp zipper-based supramolecular helical arrangement (Figure a) that changed the chirality upon dihydrogen phosphate binding (Figure b) . These Trp-appended bis-urea peptides ( 37 – 39 ) showed a vesicular assembly.…”
Section: Self-assembling Designer Pseudopeptides For Vesicular Assemblymentioning
confidence: 99%
“…The antiparallel sheet would pair the Trp with the Lys side chain (Lys8) of the same chirality, considering that the hydrophobic contacts among alkyl chains would force them to overlap each other [28, 35] . Although the cation‐π interactions have been proposed as part of protein stabilization, [36] the π–π interactions between the indole groups, as confirmed by the strong CD band at ≈230 nm attributed to the interaction between Trp side chains, [31, 32] corroborated this preference.…”
Section: Resultsmentioning
confidence: 92%
“…Since these bands originate from the interaction of the Trp residues with the peptide skeleton and the stacking of the aromatic chromophores (Trp exciton‐coupled bands), [31] such an increase in the CD signal under physiological conditions suggests that the resulting nanotubes are stabilized by salt‐bridge interactions, in which the Trp residues are located nearby one another, allowing for staking among them and giving rise to the intense aromatic CD bands. However, in the case of the CPDaTn ( n =10, 14), the CD spectra displayed an opposite Cotton effect, implying a different helical orientation of the Trp side chains in the supramolecular structure (Figure S6) [32] . This can be related with the close proximity of the ammonium groups to the nanotube surface forcing some deviations on the β‐sheet structure of the nanotube that modify the relative packing of indole moieties.…”
Section: Resultsmentioning
confidence: 98%
“…Switchable chiroptical materials are of great interest in applications for data storages, sensors, optical switches, optical displays, and light modulators. Chiroptical activity can be modulated reversibly by external stimuli, such as pH, heat, light irradiation, and electricity. Although many studies on chiroptical switches triggered by the photochromism and photoisomerization have been reported, , there are few reports about the electro-driven chiroptic switch based on the electrochromism. , Among the variety of materials showing electrochromism, conjugated polymers are one of the most attractive electrochromic materials because of their solution processability, fast response time, and multiple colors . Reynolds and co-workers have reported that the electrochromic devices using a series of polythiophene , and polypyrrole (PPy) derivatives show excellent electrochromic properties and beautiful colors. , Chiral sensors consisting of optically active conjugated polymers have been studied. …”
Section: Introductionmentioning
confidence: 99%